The quadruplex r(CGG)(n) destabilizing cationic porphyrin TMPyP4 cooperates with hnRNPs to increase the translation efficiency of fragile X premutation mRNA - Ofer, Noa (Oxford University Press, 2009)
The 5′ untranslated region of the FMR1 gene which normally includes 4–55 d(CGG) repeats expands to > 55–200 repeats in carriers of fragile X syndrome premutation. Although the levels of premutation FMR1 mRNA in carrier cells are 5–10-fold higher than normal, the amount of the product FMR protein is unchanged or reduced. We demonstrated previously that premutation r(CGG)(n) tracts formed quadruplex structures that impeded translation and lowered the efficiency of protein synthesis. Normal translation could be restored in vivo by the quadruplex r(CGG)(n) destabilizing action of CBF-A and hnRNP A2 proteins. Here we report that the quadruplex-interacting cationic porphyrin TMPyP4 by itself and in cooperation with CBF-A or hnRNP A2 also unfolded quadruplex r(CGG)(n) and increased the efficiency of translation of 5′-(CGG)(99) containing reporter firefly (FL) mRNA. TMPyP4 destabilized in vitro a (CGG)(33) intramolecular quadruplex structure and enhanced the translation of 5′-(CGG)(99)-FL mRNA in a rabbit reticulocyte lysate and in HEK293 cells. The efficiency of translation of (CGG)(99)-FL mRNA was additively increased in cells exposed to TMPyP4 together with CBF-A. Whereas low doses of TMPyP4, CBF-A or hnRNP A2 by themselves did not affect the in vivo utilization of (CGG)(99)-FL mRNA, introduction of TMPyP4 together with either protein synergistically augmented its translation efficiency.